2001
DOI: 10.1093/jn/131.9.2329
|View full text |Cite
|
Sign up to set email alerts
|

Starch Digestion Rate in the Small Intestine of Broiler Chickens Differs among Feedstuffs

Abstract: Dietary starch is the major energy source for broiler chickens, and knowledge about its digestive behavior can be important. In a digestibility trial with 720 broiler chickens, site, rate and extent of starch digestion were measured for 12 feedstuffs. Starch digestion was determined using the slaughter technique, which involves removal of the small intestine from the recently killed chicken, with manual collection of the contents. Starch digestion coefficients were calculated from remaining starch in three seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(89 citation statements)
references
References 19 publications
7
78
0
4
Order By: Relevance
“…However, earlier studies have illustrated that decreasing sorghum particle size can improve both starch and protein digestibility (Luce et al, 1970). The in vitro digestibility of starch in cassava, wheat, maize and sorghum has been shown to be 92.1, 84.1, 74.6 and 69.4%, respectively (Weurding et al, 2001).…”
Section: Amino Acidsmentioning
confidence: 99%
“…However, earlier studies have illustrated that decreasing sorghum particle size can improve both starch and protein digestibility (Luce et al, 1970). The in vitro digestibility of starch in cassava, wheat, maize and sorghum has been shown to be 92.1, 84.1, 74.6 and 69.4%, respectively (Weurding et al, 2001).…”
Section: Amino Acidsmentioning
confidence: 99%
“…For instance, an elevated apparent digestibility coefficient within the 0·5 region suggests enhanced digestion and a more rapid uptake of glucose. However, it is unclear whether a diet containing rapidly, in contrast to slowly, digestible starch is more beneficial for the piglet, although there is some evidence that the latter may lead to better overall performance in broiler chickens (6) . In contrast, a low apparent digestibility coefficient indicates that a significant amount of starch has escaped digestion in the small intestine and is subsequently available for fermentation within the large intestine (7) .…”
Section: Piglets: Cereals: Starch Digestibility: Prediction: In Vitromentioning
confidence: 99%
“…Extensive studies have shown that the digestibility of dietary carbohydrates in swine is largely affected by their source, structure and composition as well as by the activities of digestive enzymes (Cone and Vlot, 1990;Franco et al, 1992;Leclere et al, 1993;Weurding et al, 2001). Much evidence also showed that the rate of glucose absorption was tested from the portal vein of pigs (Rerat, 1985;Vaugelade et al, 1994;van der Meulen et al, 1997).…”
Section: Introductionmentioning
confidence: 99%